The Implementation of Rehabilitation against Narcotics Abuser - Noorul Umaya; Latifah Hanim; R. Sugiharto Sugiharto (Universitas Islam Sultan Agung, 2022)
The purpose of this study is to find out and analyze the implementation of rehabilitation for narcotics abusers, to find out and analyze the obstacles faced by the Public Prosecutor in implementing the rehabilitation of narcotics abusers and their solutions. The research approach method used is the sociological juridical method. The conclusion of this study is that the implementation of rehabilitation for narcotics abusers is carried out entirely by the National Narcotics Agency (BNN). The obstacles faced by the Public Prosecutor in implementing rehabilitation are the absence of juridical qualifications between the types of criminal offenses and violations, the absence of a special rehabilitation center for narcotics abusers, the lack of rehabilitation technicians and the limited rehabilitation budget owned by the National Narcotics Agency (BNN).